ANALISIS KOMPARASI PEMILIHAN LAMPU PENERANGAN JALAN TOL - Sri Pringatun; - Karnoto; M. Toni Prasetyo (PSTE UNIMUS, 2011)
Street lighting is an integral part of the highway construction. The main purpose of highway lighting is to produce the speed, accuracy, and comfort of vision at night time, keep the quality of visibility, and makes it easier for passing vehicles. Highway lighting function other thanto enhance rider safety and comfort, especially in anticipation of situations traveling at night also for environmental safety or to prevent crime and to provide comfort and beauty of the surroundings. This research activity begins with the collection of data on the kind of - kind of street lighting, lighting as well as the formulation of data - other data you need, and then do the calculation and analysis of the data - the data obtained. The results that the lights SON - T 150 W at 19:43 lux illumination values and SON lamps - T 250 W value of 36.27 lux illumination, the totalpower of 19,050 W, PLN subscription fee of Rp. 25,575,000.00, electric bill per month USD. 6,069,330.00, the investment cost of Rp.196,567,800.00. By using the method of comparative analysis it can be concluded that the selection of lamps SON - T as highway lighting Semarang - Semarang Solo Ruas Phase I - Section I Bawen Tembalang - Gedawang is the best.Keywords: highway lighting lamps, SON - T, Comparison.